The content of mathematics books prescribed for the lower primary stage according to the creative solution skills of verbal problems (Journal of the College of Basic Education, 2023)
Summary of the research:The aim of the research is to analyze the content of mathematics books for the lower primary stage according to the creative solution skills of verbal problems, and to verify the objective of the current research, the following questions were derived:1) What is the percentage of availability of creative solution skills for verbal problems in the content of the mathematics textbook for the first grade of primary school?2) What is the percentage of the availability of creative solution skills for verbal problems in the content of the mathematics textbook for the second grade of primary school?3) What is the percentage of availability of creative solution skills for verbal problems in the content of the mathematics textbook for the third grade of primary school?4) What is the percentage of availability of creative solution skills for verbal problems in the content of mathematics books prescribed for the lower primary stage?In order to achieve the goal of the current research, the two researchers adopted the analytical descriptive approach, and the research community was determined by the content of mathematics books prescribed for the lower primary stage. The main and sub-verbal skills and the indicators indicating them, as the number of main skills reached (3) skills and (10) sub-skills and (31) indicative indicators. The validity of the tool was verified by presenting it to the arbitrators. The explicit and implicit idea was adopted as a unit of analysis, and the frequencies, percentages, and Holesti equation) as statistical means.1) The content of the mathematics books prescribed for the lower primary stage contains low rates of creative solution skills for verbal problems, as its repetitions in all the content of the aforementioned three books amounted to (2905) repetitions.2) The skill (understanding the issue) ranked first in the content of each book of mathematics prescribed for the lower primary stage, followed by the skill (generating ideas) in the second place, then the skill (implementation planning) in the third place. In the light of the results of the research, the two researchers recommended a review of the formulation of the content of the mathematics books prescribed for the lower primary stage, by employing the skills of creative solution to verbal issues in high proportions and equal in their content. and the extent to which students acquire it.Keywords: content analysis, creative solution skills for verbal problems.